Strategic sustainable development of tourism industry in Malaysia - Ismail, Othman; Ahmad, Norafifah (2004)
The growing importance of sustainable development in tourism sector has been well documented and discussed by politicians, researchers and academics alike.The nucleuses of their discussions stem from the perspectives of the hosts, the tourists, and their impacts on tourism.This paper however will shed some lights on the importance of tourism in the context of Agenda 21, which focuses on the physical development that affects the environment and the community.Irrevocable damages to the environment caused by irresponsible physical development have become very sensitive and much-debated issues to most developing nations.Thus sustainable development has become an important strategy, designed to facilitate a move towards sustainability by increasing the benefits and decreasing the cost of tourism development.Sustainable tourism development in this context is the development within a designated area (community and/or environment) in such a manner and at such a scale that it remains viable over an indefinite period, and does not degrade or alter the human and physical environment.This paper explores sustainable tourism development process from three different perspectives, namely those from local residents, tourists, and agencies directly or indirectly related to the tourism development.Given the complexity and diversity of the sustainable development concept, this study has adopted a tool that was developed by Prescott- Allen (1995) using Barometer of Tourism Sustainability (BTS).Sustainable status requires an average of 8 point on a 10-point meter scale. Results from the three perspectives produced an average of 6.66 with inferences made on several related issues pertaining to sustainable tourism development in Malaysia.The underlying philosophy of sustainable tourism development appears to embrace the notion of holistic approach.It requires the cooperation and integrated efforts among the three stakeholders: the host community, the visitors, and the authorities concerned for the management and development of a destination.